The Multi-Fungicide Resistance Status of Aspergillus fumigatus Populations in Arable Soils and the Wider European Environment - Fraaije, Bart; Atkins, Sarah; Hanley, Steve; Macdonald, Andy; Lucas, John (Frontiers in Microbiology, 2020)
The evolution and spread of pan-azole resistance alleles in clinical and environmental isolates of Aspergillus fumigatus is a global human health concern. The identification of hotspots for azole resistance development in the wider environment can inform optimal measures to counteract further spread by minimising exposure to azole fungicides and reducing inoculum build-up and pathogen dispersal. We investigated the fungicide sensitivity status of soil populations sampled from arable crops and the wider environment and compared these with urban airborne populations. Low levels of azole resistance were observed for isolates carrying the CYP51A variant F46Y/M172V/E427K, all belonging to a cluster of related cell surface protein (CSP) types which included t07, t08, t13, t15, t19 and t02B, a new allele. High levels of resistance were found in soil isolates carrying CYP51A variants TR34/L98H and TR46/Y121F/T289A, all belonging to CSP types t01, t02, t04B or t11. TR46/Y121F/M172V/T289A/G448S (CSP t01) and TR46/Y121F/T289A/S363P/I364V/G448S (CSP t01), a new haplotype associated with high levels of resistance, were isolated from Dutch urban air samples, indicating azole resistance evolution is ongoing. Based on low numbers of pan-azole resistant isolates and lack of new genotypes in soils of fungicide-treated commercial and experimental wheat crops, we consider arable crop production as a coldspot for azole resistance development, in contrast to previously reported flower bulb waste heaps. This study also shows that, in addition to azole resistance, several lineages of A. fumigatus carrying TR-based CYP51A variants have also developed acquired resistance to methyl benzimidazole carbamate, quinone outside inhibitor and succinate dehydrogenase (Sdh) inhibitor fungicides through target-site alterations in the corresponding fungicide target proteins; beta-tubulin (F200Y), cytochrome b (G143A) and Sdh subunit B (H270Y and H270R), respectively. Molecular typing showed that several multi-fungicide resistant strains found in agricultural soils in this study were clonal as identical isolates have been found earlier in the environment and/or in patients. Further research on the spread of different fungicide-resistant alleles from the wider environment to patients and vice versa can inform optimal practices to tackle the further spread of antifungal resistance in A. fumigatus populations and to safeguard the efficacy of azoles for future treatment of invasive aspergillosis.